PENGARUH KEPEMIMPINAN DAN MANAJERIAL SKILL KETUA KELOMPOK TERHADAP KEBERDAYAAN KELOMPOK TANI DAN DAMPAKNYA TERHADAP KEBERHASILAN USAHA TANI PETANI ANGGOTA - Supriadi, Dede Asep; Sukmawati, Dety; Permana, Nendah Siti (Universitas Majalengka, 2024)
This study aims to determine the influence of Leadership and Managerial skills of Farmer Group leaders on Farmer Empowerment and their impact on productivity and income of rice farming. This study used a survey method of lowland rice farmers in Warungkondang District, Cianjur Regency. Respondents were assigned randomly stratified proportions using the Slovin formula and a total of 70 farmers were selected. The form of research is verification and the analysis technique used is path analysis and Chi Square. Based on the research results obtained. Performance Farmer group leadership consists of dimensions: Smart; Responsibility; Honest; trusted; Consistent; Initiative; and Firmly obtained an achievement level of 76.89% good criterion. Performance of Managerial Skills Head of farmer groups consisting of dimensions: production managerial; financial managerial; Managerial Human Resources; Marketing managerial achievement level obtained 79.32% good criterion. Performance of the empowerment of group members consisting of dimensions: Accessibility, Independence, Protection, Participation and Fulfillment of Needs to obtain an achievement level of 75.81% good criteria. There is a positive correlation between the leadership of group leaders and the managerial skills of group leaders as shown by the correlation coefficient r = 0.78. It is interpreted that the higher the leadership, the higher the managerial skills of the farmer group leaders. There is a positive influence of the Leadership and Managerial Skill of the Chair of the farmer group on the empowerment of group members. The magnitude of the respective influence is 56.46% and 22.80%. The empowerment of farmer group members influences the productivity of lowland rice farming. The higher the level of farmer empowerment, the higher the productivity of the farming business. The empowerment of farmer group members influences the achievement of lowland rice farming income. The higher the level of empowerment of farmers, the higher the income of farming